2006
DOI: 10.1167/iovs.06-0024
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Flow-Mediated Vasodilation in Normal-Tension Glaucoma Using a Noninvasive Determination for Peripheral Endothelial Dysfunction

Abstract: This study demonstrated impaired FMD in patients with NTG and the results provide evidence of a generalized peripheral vascular endothelial dysfunction in patients with NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 32 publications
3
39
0
3
Order By: Relevance
“…It is often used to determine cardiovascular disease risk factors in cardiovascular research (Anderson et al, 2000), but more recently has also been adopted in ophthalmological studies to investigate peripheral vascular endothelial functionality in glaucoma patients (Su et al, 2008), in NTG (Su et al, 2006) and pseudoexfoliative syndrome (Atalar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is often used to determine cardiovascular disease risk factors in cardiovascular research (Anderson et al, 2000), but more recently has also been adopted in ophthalmological studies to investigate peripheral vascular endothelial functionality in glaucoma patients (Su et al, 2008), in NTG (Su et al, 2006) and pseudoexfoliative syndrome (Atalar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…29,[31][32][33] The results about plasma hsCRP levels in normal tension glaucoma are controversial. Su et al 16 reported no difference in the hsCRP level between normal tension glaucoma and controls after exclusion of patients with cardiovascular and other systemic diseases and they suggested that systemic vascular inflammation may not be a major cause in pathogenesis of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that there could be intra-observer differences in measurements. However, previous studies showed that intra-observed differences are minimal without significant effect on results [9,10]. In our study, an experienced cardiologist performed measurements.…”
Section: Discussionmentioning
confidence: 72%